Salt Production Activities in Izmir Çamaltı Saltern and in Turkey (1923-1950) / İzmir Çamaltı Tuzlası ve Türkiyede Tuz Üretimi Çalışmaları (1923-1950) - Yurtoğlu, Nadir (Karabuk University, 2018)
AbstractThis study deals with salt production activities in Izmir Camalti Saltern and in Turkey in the Republic period and their contributions to economy. Data has been obtained by scanning the literature. The subject is limited to and discussed under the title of salt production activities in Izmir Camalti Saltern and in Turkey in the period of Republican People’s Party (CHP) (1923-1950). Evaluations have been made based on numeric data in discussing the salt production activities in Izmir Camalti Saltern and in Turkey. The gap in the literature about the research subject has been filled through use of primary sources such as Republic archive documents, official publications, journals of laws, journals of official reports, proceedings of memorandum, official gazettes, statistical data, Ayin Tarihi journal (government’s dating publication), and articles from the magazines of the period. The relevant evaluations have been made considering the production processes in Turkey and those in the leading countries in the world about salt production. It has been found out that salt production, sales, and export were monopolized by the state with the General Directorate of Salt Monopoly set up on 1 June 1927 with its center in Ankara. With the modernization of Camalti Saltern and other facilities established from that date on, the amount of salt production in Turkey and salt export to other countries increased, thereby making substantial contributions to the national economy.OzBu arastirmada Cumhuriyet doneminde Izmir Camalti Tuzlasi ve Turkiye’de tuz uretimi faaliyetleri ile bunun ekonomiye olan katkilari ele alinmistir. Veriler literatur taramasi yoluyla elde edilmistir. Konu, Cumhuriyet Halk Partisi (CHP) doneminde Camalti Tuzlasinda ve Turkiye’de tuz uretimi faaliyetleri (1923-1950) ile sinirlandirilmis ve bu baslik etrafinda incelenmistir. Camalti tuzlasi ve Turkiye’de tuz uretimi calismalari ele alinirken sayisal veriler uzerinde degerlendirmeler yapilmistir. Arastirmanin konusu hakkinda literaturde yer alan bosluklar Cumhuriyet arsivi belgeleri, resmi yayinlardan kanunlar ve tutanak dergileri, zabit ceridesi, resmi gazete, istatistik verileri, ayin tarihi ve donemin sureli yayinlarindan olan dergilerinin makaleleri gibi birincil kaynaklarin kullanilmasi yoluyla tamamlanmistir. Calismanin konusu incelenirken donemin Turkiye’si ile dunyanin tuz uretimi konusunda onde gelen ulkelerin uretim surecleri goz onune getirilerek degerlendirmeler yapilmistir. Calismada elde edilen sonuc sudur: 1 Haziran 1927 tarihinde merkezi Ankara olarak kurulan Tuz Inhisari Umumi Muduriyeti ile tuz uretimi, satisi ve ihracati devlet tekeline alinmistir. Bu tarihten itibaren Camalti Tuzlasinin modernlestirilmesi ve kurulan tesisleri sayesinde Turkiye’de tuz uretimi ve dis ulkelere yapilan tuz ihracati miktari artirilmis bu suretle ulke ekonomisine onemli katkilar saglanmistir.